The Role of Digital Strategy in Enhancing Strategic Behavior: A Case Study in the Ministry of Foreign Affairs - Assistant Techer. Muhammad Yahya Jihad *; Assistant Techer. Roxanne Jamal Shukor; Dr. Khaled Zghitoun Globe (مجلة الدراسات الاقتصادية والادارية)
The research aims to examine the impact of digital strategy on enhancing strategic behavior within the Ministry of Foreign Affairs, focusing on how digital technology and artificial intelligence can improve the strategic decision-making process and organizational work behaviors. The study highlights the concept of digital strategy as a modern tool that enhances the capacity of governmental institutions to adapt to digital transformations and achieve their strategic objectives. It also establishes a connection between the use of advanced digital tools and the elevation of strategic behavior levels among leadership. The research adopted a theoretical framework that defines the concepts of digital strategy and strategic behavior, analyzing their key dimensions. On the practical side, a field study was conducted involving a purposive sample of 173 strategic leaders within the Ministry of Foreign Affairs, selected based on their expertise and use of digital technology in their work. Data were collected through a specially designed questionnaire, supplemented by personal interviews, and analyzed using modern statistical tools (SPSS V.24). The findings reveal that the digital strategy has a positive and significant impact on enhancing strategic behavior within the ministry. The results indicate that the use of digital tools and modern technology contributes to improving leadership capabilities in data analysis, risk prediction, informed decision-making, and effective strategic planning. Furthermore, the digital strategy enhances the ministry's flexibility and its ability to adapt and grow in the face of international challenges.